2021
DOI: 10.3390/e23020152
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Management and Modeling of Forced Convection and Entropy Generation in a Vented Cavity by Simultaneous Use of a Curved Porous Layer and Magnetic Field

Abstract: The effects of using a partly curved porous layer on the thermal management and entropy generation features are studied in a ventilated cavity filled with hybrid nanofluid under the effects of inclined magnetic field by using finite volume method. This study is performed for the range of pertinent parameters of Reynolds number (100≤Re≤1000), magnetic field strength (0≤Ha≤80), permeability of porous region (10−4≤Da≤5×10−2), porous layer height (0.15H≤tp≤0.45H), porous layer position (0.25H≤yp≤0.45H), and curvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Rosca and Pop [25] studied hybrid nanofluid flows determined by a permeable power-Law stretching/shrinking sheet modulated by orthogonal surface shear. Selimefendigil and Oztop [26] examined thermal management and modeling of forced convection and entropy generation in a vented cavity by simultaneous use of a curved porous layer and magnetic field. Jamshed studied [27] the numerical investigation of MHD impact on Maxwell nanofluid.…”
Section: Eejp 2 (2023)mentioning
confidence: 99%
“…Rosca and Pop [25] studied hybrid nanofluid flows determined by a permeable power-Law stretching/shrinking sheet modulated by orthogonal surface shear. Selimefendigil and Oztop [26] examined thermal management and modeling of forced convection and entropy generation in a vented cavity by simultaneous use of a curved porous layer and magnetic field. Jamshed studied [27] the numerical investigation of MHD impact on Maxwell nanofluid.…”
Section: Eejp 2 (2023)mentioning
confidence: 99%
“…Selimefendigil and Öztop 32 used the finite volume method to study how a partially curved layer with tiny pores (porous layer) affects heat transfer and the creation of disorder (entropy) in a ventilated space filled with a fluid containing a mixture of nanoparticles (hybrid nanofluid). The study also considered the influence of an angled magnetic field on this system.…”
Section: Introductionmentioning
confidence: 99%
“…Their result showed that growth of the porous layer height leads to a reduction of the heat transfer rate. Selimefendigil and Öztop [44] studied the curved porous layer impact on forced convection heat transfer and entropy generation in a vented cavity filled with hybrid nanofluid under inclined magnetic field effects by using the finite volume method. Gibanov et al [45] examined MHD mixed convection in a lid-driven cavity partially filled with a porous medium saturated with a ferrofluid.…”
Section: Introductionmentioning
confidence: 99%